2003
DOI: 10.1128/jcm.41.7.2968-2973.2003
|View full text |Cite
|
Sign up to set email alerts
|

Continued Low Rates of Transmission of Mycobacterium tuberculosis in Norway

Abstract: In this study, we determined the genetic diversity of Mycobacterium tuberculosis isolated in Norway from 1999 to 2001. The results were compared to those for strains isolated from 1994 to 1998. A total of 818 patients were diagnosed with tuberculosis (TB) during the last 3-year period. Of these cases, 576 (70%) were verified by culturing, and strains from 551 patients (96%) were analyzed by the IS6110 restriction fragment length polymorphism (RFLP) method. We excluded 13 strains (2.4%) from the analyses, since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 21 publications
2
52
2
3
Order By: Relevance
“…Immigration from countries with high rates of TB to countries with lower rates is a phenomenon which has affected different European and North American countries for quite some time (6,8,12,(16)(17)(18)22). This obviously has an impact on the epidemiological features of TB of the host countries, and therefore the recent transmission patterns of TB are expected to be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Immigration from countries with high rates of TB to countries with lower rates is a phenomenon which has affected different European and North American countries for quite some time (6,8,12,(16)(17)(18)22). This obviously has an impact on the epidemiological features of TB of the host countries, and therefore the recent transmission patterns of TB are expected to be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment and improvement of cost-effectiveness TB screening programmes are currently the subject of debate because of their costs and public health impact [11,51,[76][77][78][79]. Recent analysis of the cost-effectiveness of screening programmes concluded that current radiographic screening programmes have minimal impact and are not cost-effective [81].…”
Section: Requirement For Improved Datamentioning
confidence: 99%
“…2) Recent TB infection or reinfection due to travel to the home country [7][8][9]. 3) Recent infection or reinfection within the new country that is related to local exposure and social mixing [6,[10][11][12].…”
mentioning
confidence: 99%
“…Interestingly, we suspect that in some incidences, native Korean TB patients may be the source of infection for foreign-born TB patients, as K family strains endemic in Korea (Kim et al, 2001;Park et al, 2000) were identified in foreign-born TB patients. A previous study in Norway also found that outbreaks of TB involving foreign-born individuals were often determined to be of Norwegian origin (Dahle et al, 2003). The origin of strains uncommon in Korea was less clear; some strains, especially those with high RFLP copy numbers, resembled a modern Beijing family type that may have potential for global transmission as they have been identified in multiple countries surrounding Korea (Kang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%